2015
DOI: 10.1161/strokeaha.115.009522
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Versus Distributed Aphasia Therapy

Abstract: T reatment intensity is an important consideration for the delivery of effective and efficient aphasia rehabilitation services. However, the optimal treatment intensity for aphasia rehabilitation is unknown.1 Neuroscience research suggests that intensive training is required to optimize neurological and functional recovery post stroke.2 Within the field of cognitive psychology, however, there is considerable evidence supporting the distributed practice effect, which suggests that optimal long-term learning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…The relationship between treatment dosage and functional improvement is not straightforward. Restated, more does not always equate to better, and research in post-stroke motor [188] and language [189] function confirm this assertion. The VECTORS study randomized subjects with acute stroke to traditional upper-extremity therapy, dose-matched CIMT, or high-intensity CIMT [188].…”
Section: Brain Repair and Treatment Considerationsmentioning
confidence: 99%
“…The relationship between treatment dosage and functional improvement is not straightforward. Restated, more does not always equate to better, and research in post-stroke motor [188] and language [189] function confirm this assertion. The VECTORS study randomized subjects with acute stroke to traditional upper-extremity therapy, dose-matched CIMT, or high-intensity CIMT [188].…”
Section: Brain Repair and Treatment Considerationsmentioning
confidence: 99%
“…The question of whether increasing the intensity of rehabilitation is beneficial to outcomes has been a focus of traditional rehabilitation studies. While it is logical to assume that more intensive treatment results in greater outcomes and has been demonstrated in chronic (Bhogal et al, 2003a , b ; Cherney et al, 2008 ) and in acute patients with aphasia (Godecke et al, 2014 ); other studies have questioned this premise (Bakheit et al, 2007 ; Dignam et al, 2015 ). For instance, a randomized controlled trial found that intensive treatment (up to 5 h/week) was no better than standard treatment (1–2 h/week) (Bakheit et al, 2007 ).…”
Section: Questions That Can Now Be Examinedmentioning
confidence: 99%
“…Some studies showed that CIAT with less constraint and less intensity still had the similar effect on post-stroke chronic aphasia [ 36 , 37 ]. A study comparing the intensive and distributed speech therapy gave a conclusion that intensive speech therapy may be not better than distributed speech therapy with the same dosage [ 38 ]. Thus, an increasing number of studies started to pay more attention to the difference between the CIAT with other speech therapy programs delivered in the same intensity, and tried to explain which component of the CIAT is useful.…”
Section: Introductionmentioning
confidence: 99%